Craft Entrepreneurship on Environmental Waste Recycling in Malang Municipality - Sri Muljaningsih (Sebelas Maret Business Review, 2018)
The purpose of this study is to examine the effectiveness of Sanggar Asta Karya Panca Wiguna (AKPW) in Malang Municipality, Indonesia, in garbage-recycling business. Garbage has been turned into valuable and artistic products that is also environmentally friendly. The products produced include dammar kambang, suket wayang, lampshade, and others. This study uses qualitative method to examine the entrepreneurship behaviour of the AKPW. The key informant is the chairperson of the studio. AKPW works in the fields of environment, education, economy, culture, and health. The result of the research shows that the garbage-recycling business takes creativity and product innovation based on persistence and perseverance. AKPW works on the concept of social green entrepreneurship that combines the concept of three pillars of ecological, economic, and social sustainability through art and culture. AKPW should conduct more efforts to socialize more intensively.